Estudio de valores hemáticos y proteicos en relación al estado nutricional de Adultos Mayores que acuden a la Institución Hogar de EMAUS. - Cabrera Jaramillo, Maricela Elizabeth (2013)
STUDY OF VALUES AND HEMÁTICOS PROTEIN IN RELATION TO THE NUTRITIONAL STATUS OF OLDER ADULTS WHO COME TO THE INSTITUTION HOME OF EMMAUS. The study corresponds to a descriptive design prospective, cross sectional in 50 older adults 65 years of the institution of Social Service "HOME ON THE ROAD TO EMMAUS" of the city of Loja. The study corresponds to a descriptive design prospective, cross sectional in 50 older adults 65 years of the institution of Social Service "HOME ON THE ROAD TO EMMAUS" of the city of Loja, , Who went to the home institution of EMMAUS in the city of Loja, during the period March - April 2013; Obtaining as a result of the older adults, That 16% engage physical exercise, with 2% overweight; 92% presents a balanced diet with a 6% overweight; 24% shows a lack of teeth and a normal weight, the 30% has metabolic diseases and have a 2% overweight. In the determination of the haematological values: the red blood cells in a 2% were decreased, hematocrit and hemoglobin is presented in a 6% diminished; the total protein resulted in a 8% decreased; albumin and globulins are 100% normal. Key Words: GR Red Blood Cells; Hct Hematocrit; Hb Hemoglobin; ICM: Body Mass Index.